PENGARUH HALLYU TERHADAP KEPUTUSAN PEMBELIAN PRODUK KREATIF LOKAL ALA KOREA (STUDI KASUS ANGGOTA CPN, FANFICT GC, DAN KPOPERS PEKANBARU) - Lina Badriana; Gimin Gimin; Gani Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the Hallyu influence on the decision to purchase Korean-style local creative products for members of the CPN group, Fanfict GC group, and Pekanbaru Kpopers conducted in March 2019. The study was conducted with an unknown population and a sample of 100 people taken by incidental sampling quota technique. The technique used to obtain data is by distributing questionnaires. The method used is descriptive quantitative. In the descriptive analysis test, purchasing decisions are mostly included in the medium category, which is 72% and Hallyu is also in the moderate category of 51%. Based on the results of the analysis, it was found that Hallyu had a significant effect on the decision to purchase Korean-style local creative products in members of the CPN, Fanfict GC and Kpopers Pekanbaru groups with Fcount of 13.303 (13.303> 3.94) and the equation Y = 18.633 + 0.343X. The determination (R2) or Hallyu contribution to the decision to purchase Korean-style local creative products for members of the CPN, Fanfict GC, and Kpopers Pekanbaru groups is 12%.Key Words: Purchasing Decisions, Hallyu, Creative Products